1986
DOI: 10.1037/0022-3514.50.2.392
|View full text |Cite
|
Sign up to set email alerts
|

A theory and method of love.

Abstract: This research was part of a larger research program on love and sex attitudes. Earlier work on love was reported in Hendrick, Hendrick, Foote, and Slapion-Foote (1984). The work on love extends Lee's (1973Lee's ( /1976) theory of six basic love styles: Eros (passionate love), Ludus (game-playing love), Storge (friendship love), Pragma (logical, "shopping list" love), Mania (possessive, dependent love), and Agape (all-giving, selfless love). Theory development has proceeded concurrently with the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
650
5
100

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 747 publications
(798 citation statements)
references
References 28 publications
43
650
5
100
Order By: Relevance
“…Theory testing and construct measurement are inextricably linked. It is suggested that the development of a valid measure of the theoretical construct to be examined should be the first step in the research process (Hendrick & Hendrick, 1986). If the construct validity of the instrument is questionable, then it is not possible to accurately test the theory under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theory testing and construct measurement are inextricably linked. It is suggested that the development of a valid measure of the theoretical construct to be examined should be the first step in the research process (Hendrick & Hendrick, 1986). If the construct validity of the instrument is questionable, then it is not possible to accurately test the theory under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Third, recent developments of computer software to test the factor structures of psychological questionnaires have prompted researchers (see Hendrick and Hendrick, 1986;Schutz and Gessaroli, 1993;Bentler, 1995;Thompson and Daniel, 1996) to emphasise the benefits of structural equation modelling techniques such as Measure of mood 6 confirmatory factor analysis. The traditional method of choice to demonstrate factorial validity has been exploratory factor analysis techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Para analizar los distintos estilos de amor en los discursos del alumnado, hemos tomado la tipología de John Lee (1973), ya que ha sido ampliamente considerada en la investigación sobre el tema (Hendrick y Hendrick ,1986;Ubillos et al, 2001Ubillos et al, , 2003Ferrer et al, 2008).…”
Section: Mètodounclassified
“…Há diversas escalas que medem vínculo emocional/amor em humanos (Triangular Love Scale -Sternberg, 1986; Love Attitude Scale - Hendrick & Hendrick, 1986;Love Scale [Marriage and Relationship Questionnaire] -Russel & Wells, 1993;Tetrangular Model -Yela, 2006 (Russel & Wells, 1986). Essa escala é focada em medir o amor romântico em casais em relacionamento estável e possui a praticidade de medir vários aspectos do relacionamento em um único questionário.…”
Section: Mensuração Do Amorunclassified